Capital social et transmission du capital humain chez les femmes peulhs transformatrices de lait de vache au Bénin - JIMMY, Paul; MOUMOUNI, GUILLAUME; OKRY, Florent; Nadia, Fanou (My University, 2017)
This paper analyzes the contribution of social capital in transmission of human capital within non-formal education systems related to agriculture in Benin. The traditional dairy processing of Fulani women is concerned. Data were collected mainly through semi-structured interviews with 85 Fulani women in the District of Gogounou, Northern Benin. The results showed that bonding social capital (familial environment) predominantly intervenes in the women human capital building. Also, the linking social capital, derived from development project’intervention provides human capital reinforcement through associations and technological innovations. The transmission of human capital from mother to daughter supports the perpet-uation of this economic and cultural activity of Fulani women across generation. These results suggest that the intergenera-tional transmission of human capital of Fulani women refers to dynamic of social reproduction. The promotion of bridging social capital (women's associations) and the increasing of their contact social capital are recommended to manage modernization of their activity in order to improve food security.
Keywords: Social reproduction; agricultural foods processing; Perishable products; Fulani women; Benin